Developing Customer Relationship Management Application for Dental Clinic Using Agile Approach to Enhance Efficiency and Customer Satisfaction - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research addresses the issues of efficiency and customer satisfac-tion in dental clinics by developing a Customer Relationship Manage-ment (CRM) application using the Agile approach. The research meth-odology includes identifying the needs of dental clinics, project plan-ning, application development based on architectural design and Agile methods, functional testing, and user acceptance analysis. The re-search results indicate that the CRM application successfully meets all tested features and achieves a user satisfaction rate of 85%. The con-tribution of this research lies in developing innovative IT solutions that are responsive to the needs of dental clinics, aiming to enhance opera-tional efficiency and patient service in the dental healthcare industry.